Picobia polonica sp. n. (Acari: Prostigmata: Syringophilidae), a new species of quill mite from the domestic hen, Gallus gallus domesticus (Aves: Phasianidae) - Skoracki, M; Magowski, W; Dabert, J (Folia parasitologica, 2001)
Female, physogastric female and male of Picobia polonica sp. n. collected from the domestic hen Gallus gallus domesticus (L.) in Poland are described and the phenomenon of physogastry in this and related species is briefly discussed. Picobia polonica is similar to Picobia khulkhshani (Kivganov et Sharafat, 1995). These two species can be distinguished by the following characters: P. polonica: chelicerae dentate, each with three minute teeth; setae g1 and pg2 subequal in length; ratio pg1 : pg2, 3: 1. P. khulkhshani: chelicerae edentate; setae g1 twice shorter than pg2; ratio pg1 : pg2, 1.6: 1.
Keywords: kur domácí; Animals; Feathers; Female; mužské pohlaví; zvířata; peří; Male; Microscopy, Interference; Poland; roztoči; Chickens; ženské pohlaví; interferenční mikroskopie; Mites; Polsko